Adapting to Crisis: Migration Research During the COVID-19 Pandemic. Issue 1 (1st June 2022) - Greatrick, Aydan; Al-Waeli, Jumana; Sender, Hannah; Maioli, Susanna Corona; Li, Jin L.; Goodwin, Ellen
Abstract: This article draws on our experiences of carrying out PhD research on migration during the COVID-19 pandemic. We are all involved with the University College London Migration Research Unit (MRU), and our PhD research explores the lived experiences of migrants and people affected by migration. This is the first of two articles in this issue of Migration and Society addressing the implications of COVID-19 on migration research from the perspective of postgraduate researchers. In this article, we firstly reflect on how "crises, " including the COVID-19 pandemic, inevitably shape contexts of migration research. We then share how COVID-19 has shaped our relationship to "the field" and our formal research institutions. Finally, we share how we have adapted our methodologies in response to COVID-19 and, considering the complex ethical and practical challenges posed by this context, reflect on what it means to make methodological "adaptations" in times of overlapping crises.